(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The article refers to the demonstration of the characteristics of extreme runoff of the rivers in the context of global climate change. The dynamics of changes of the rivers’ extreme runoff and air temperatures have been studied, compared and assessed from 1960 till 2012 (case study is the relatively large rivers of Sevan Lake basin). In the studied river-basins are viewed air temperature increase and decrease of absolute maximum extreme runoff of the rivers. Therefore, it turns out that winter temperatures have contributed to a gradual melting of snow accumulated in the river basin causing reduction of absolute maximum runoff in spring. As a result, the risk of occurrence of floods have dramatically reduced.